Forecast of biofuel production and consumption in top CO2 emitting countries using a novel grey model. (10th December 2020) - Javed, Saad Ahmed; Zhu, Bangzhu; Liu, Sifeng
Abstract: Mounting environmental concerns have given rise to an increasing focus on renewable energies like biofuels. In 2018, three countries – China, the United States, and India – together emitted almost half (50.3%) of the world's CO2 emissions (billion metric tons). The current study aims to forecast biofuels' production, consumption, and self-sufficiency in these top CO2 emitting countries using a novel grey forecasting model. The study improves on an existing grey forecasting model by optimizing the model architecture (data accumulation operation and background value generation). The proposed forecasting model, EGM (1, 1, α, θ ), is a generalized form of the even form of the grey forecasting model, and its relative performance turned out to be generally superior to that of the original model. The comparative analyses of the proposed model with two forecasting models revealed that the new model's forecast accuracy is generally better than those of others. The study finds, achieving self-sufficiency in both biofuels (fuel ethanol and biodiesel) would remain a challenge for China, while the United States and India would maintain their self-sufficiency in ethanol and biodiesel, respectively, at least till 2028. The study also argues that biofuel is more likely to be a complementary fuel rather than an alternative fuel. The study helps us understand how, in the next decade, the landscapes of biofuel production and consumption are changing, and concludes with significant policy implications.